The Winning Weaning Food (WWF): The Development of a Complementary Food for Food-Insecure Infants and Young Children in Malawi - Theophilus, Rufus J. (Nutrients, 2019)
Growing evidence exists for the benefits of adequate infant and young children feeding (IYCF) practices at the weaning stage (≥ 6 months), including optimal growth, building the immune system, cognitive development, healthy food preferences, and reduced mortality and morbidity rates. However, these outcomes are not universally experienced. To ensure that a developing country such as Malawi, where recent studies have shown high rates of food insecurity and malnutrition benefits from adequate IYCF, five nutrient-dense complementary foods (Recipes 1 to 5) were developed. Standardized food processing techniques were used in the preparation and combination of Malawian indigenous food samples. The developed food recipes were assessed for nutrient density and cultural acceptability through sensory evaluations. Recipe 5 emerged as the winning weaning food (WWF), with an overall acceptability rate of 65% (mean score of 5.82 ± 0.87). Unlike theoretical analysis with the ESHA Food Processor, statistical analysis did not show that Recipe 5 met the Codex Alimentarius recommendations for macro- and micronutrients. However, it showed that the micronutrient recommendations for iron (p = 0.0001; 95%CI) and zinc (p = 1.00; 95%CI) were partially met, but not those for calcium and vitamins A and D. The prototype and outcome of this pilot study will be invaluable for interventions aimed at combating food insecurity and malnutrition in Malawi.